The complexity of family language policy decisions: The case of Cantonese and other regional Chinese varieties - Yaling, Li; Danli, Li; Xuesong, Gao (Círculo de Lingüística Aplicada a la Comunicación, 2019)
This paper explores the beliefs, attitudes, and efforts of parents with regard to the use and preservation of regional Chinese varieties including Cantonese in the region of Guangzhou, China. The study relied on a sequential mixed method approach, involving 771 parents who completed a parental questionnaire in an online survey on Chinese parents’ language ideology, practice, and management in the home domain, followed by semi-structured interviews of 10 of the surveyed participants to gather detailed data related to the questionnaire results. The study identified inconsistencies in the participants’ beliefs and actual language practice in the survey, revealing mediation by sociolinguistic complexities, national language policies, and socioeconomic conditions on family language decisions and practices. These remind us that the survival of regional Chinese varieties or linguistic varieties without official recognition requires conducive socio-political conditions, including relevant national language policies. The results also suggest that researchers should be particularly concerned by the decline of regional Chinese varieties other than Cantonese, which are not backed up by the national language policy but enjoy a similarly prestigious status to Cantonese in the region.